Extravesical Common Sheath Ureteral Reimplantation Versus Intravesical Techniques for Refluxing Duplex Systems in Children - Aboutaleb, Hamdy A.; Abouelgreed, Tamer A.; Amin, Moamen M.; Sultan, Mohamed F. (Urology Journal, 2021)
Purpose: Retrospective comparative study of the efficacy of extravesical non-dismembered common sheath ureteral reimplantation (ECSR) versus intravesical common sheath ureteral reimplantation (ICSR) techniques for the correction of vesicoureteral reflux (VUR) in complete duplex systems. Material and Methods: Between 2010 and 2019, ECSR was performed in 38 children (8 bilaterally), and the mean ages at presentation and at surgery were 31 and 57 months, respectively. The ICSR technique was performed in 25 units (25 patients). Voiding cystography and ultrasound of the kidney and bladder were performed 3 and 12 months postoperatively. We analyzed the surgical outcomes for both groups. Results: The mean follow-up times for the ECSR and ICSR groups were 15 and 18 months, respectively. The success rate of the ECSR group was 93.5% at 3 months, improving to 95.7% at an average of one year; the rate of the ICSR group was 96% at 3 months and was the same after one year, with no significant difference between the two groups (p = .66). Postoperative complications were compared in the ECSR and ICSR groups: transient contralateral VUR was seen in 5 renal units versus 4, de novo hydronephrosis was seen in 3 units versus 2, and UTIs were observed in 3 patients versus 4. Conclusion: Both (ECSR) and (ICSR) surgeries are highly successful for the correction of VUR in uncomplicated complete duplex systems. The results of the extravesical approach are comparable with those of the intravesical technique with less morbidity and a shorter hospital stay. Thus, ECSR is our preferred technique when open surgical repair is indicated. ICSR should be reserved for complicated duplex systems necessitating concomitant reconstructive surgery.